Damage and Development of Anastrepha fraterculus (Diptera: Tephritidae) in Fruits of Two Pear Cultivars - Nunes, Marcelo Z.; Boff, Mari Inês C; dos Santos, Régis S. S.; Franco, Cláudio R.; Wille, Paulo E.; da Rosa, Joatan M.; do Amarante, Cassandro V. T. (Agrociencia Uruguay, 2020)
Anastrepha fraterculus is the main horticultural pest for food crops in southern Brazil. This study aimed to identify the damage caused by this species, evaluate its development, and correlate its infestation rate with physical and chemical characteristics of Packhams and Williams pear fruit cultivars at five different stages of development. In the field, cages were installed on branches of the pear plants in which two couples of A. fraterculus were released for a period of 48 hours. The damage resulting from oviposition was evaluated at fifteen-day intervals from the day the insects were released until harvest. The evaluation of damage consisted of visual observation of decayed and deformed fruits and the presence of larvae. In the laboratory, two couples were individualized with one fruit in a 750 mL pot for 48 hours. The evaluations consisted of counting the number of living third-instar larvae, pupae and adults. The physical and chemical analyses consisted of the determination of fruit peel and pulp texture, color, soluble solid content and transversal diameter. The incidence of the fruit fly on Packhams and Williams fruits occurred when fruits measured 54.9 and 52.8 mm respectively. The development of A. fraterculus in pear fruits of both cultivars is related mainly to fruit peel and pulp hardness.